Comparing mathematics educational values of Turkish and South Korean students using a two-step cluster analysis - DEDE, Yüksel; Kim, Hee-Jeong; Kaya, Gürcan; Akçakın, Veysel (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
A part of a larger study, this study reports on a cultural comparison of mathematics educational values of Grade 9 students in Türkiye and Korea. Building on the premise that culture, on the one hand, shapes education and, on the other hand, is influenced by it, the study seeks to explore the differences and similarities in students’ values concerning mathematics education in two somewhat different cultures, thus gaining a deeper understanding of these values from a sociocultural perspective. In this study, the mathematics educational values questionnaire of Dede and Barkatsas (2019)was used as a data collection tool. The data was analyzed using the two-step clustering analysis. The results showed that the Grade 9 students in both countries were divided into two groups regarding mathematics educational values. While the students in both countries were grouped, the practice value was the most important value when learning mathematics. In addition, it was also determined that, unlike students in Korea, the relevance value in Türkiye and the learning approach, feedback, and consolidating values in Korea were more important in grouping students. In addition, the information and communication technology [ICT] value was found to be equally important in determining the clusters of students in the two countries.